Youssef’s Syndrome - a complication of corrective surgery for mullerian anomaly - Mishra, Vineet; Saini, Suwa; Aggarwal, Rohina; Roy, Priyankur; Hokabaj, Shaheen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
The presence of cervicovaginal agenesis with unicornuate uterus is a very rare mullerian anomaly. Presence of functioning unicornuate uterus poses as a great challenge for gynecologist, because a successful repair could restore normal menses and may preserve the patient’s fertility. Though, a complication of this surgery (utero-vaginal anastomosis) is Youssef’s Syndrome. We, hereby report a case of 16 year old unmarried female with complete cervicovaginal agenesis with unicornuate uterus, who initially underwent vaginoplasty (McIndoe’s) along with uterovaginal anastomosis in order to preserve her uterus, but subsequently required hysterectomy due to Youssef’s Syndrome.